Contribution of Kurash Sport in Improving Students’ Sports Achievement in DKI Jakarta - Ahmad Budidarma; Julizar Idris; Satri Dwi Kurnia Nasution; Mukodas Arif Subekti; Ahmad Khanali (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to analyze the contribution of kurash to improving student athletic performance in Jakarta. The research approach employs a qualitative method with a descriptive-analytical design. Data were collected through literature review, limited observation, and interviews with coaches, physical education teachers, and sports organization officials. The results indicate that kurash makes a significant contribution to improving students’ physical, mental, and character development, which impacts their athletic performance. Additionally, kurash plays a role in fostering discipline, sportsmanship, and self-confidence among students. However, this contribution remains suboptimal due to limited institutional support, insufficient integration into the education system, and the absence of specific policies. This study recommends strengthening the synergy between schools, sports organizations, and local governments to optimize the role of kurash in fostering student achievement